Recanalization of an atretic left internal mammary graft after bypass surgery for an anomalous left main coronary artery origin: a case report. Issue 1 (19th December 2018) - Meredith, Thomas; Jansz, Paul; Sesel, Kenneth; Kathir, Krishna
Abstract: Background: The inter-arterial anomalous course of the left main coronary artery (LMCA) originating from the right coronary sinus of Valsalva is a rare, though potentially lethal pathology. Coronary artery bypass grafting is a potential surgical therapy with previously reported success, however, there is concern for the possibility of graft occlusion in the setting of competitive native vessel flow. Case summary: A 48-year-old gentleman presented to our facility with a non-ST elevation acute coronary syndrome. A malignant anomalous course of the LMCA was confirmed using invasive coronary angiography and computed tomography (CT). The patient underwent surgical revascularization of the left anterior descending artery with a left internal mammary artery (LIMA) graft, which was found to be atretic on follow-up CT. Seven years later the patient underwent repeat CT imaging, which confirmed recanalization of the previously atretic LIMA. Discussion: We present the first documented case of a patient with spontaneous recanalization of an occluded LIMA following bypass surgery for an inter-arterial anomalous course of the LMCA. We postulate that the dynamic obstruction of the anomalous LMCA led to variable flow dependence on the bypass graft and subsequent atresia of the LIMA, due to the favourable native flow conditions in the absence of significant obstructive coronary disease. The exact mechanism of LIMA recanalization remains unclear, but in our case may have been partly mediated by a small increase in left main plaque.